TYPE AND DENSITY OF EPIDENDRITIC PERIPHYTON IN THE SWAMP SAWAH VILLAGE NORTH KAMPAR DISTRICT - Lisbatul Khoiriyah; Nur El Fajri; Adriman Adriman (Berkala Perikanan Terubuk, 2019)
In the Swamp of Sawah Village has waters surrounded by trees and aquatic plants, which function to attach periphyton organisms. Because there are many wood submerged in swamp, the substrate used is a wood substrate (epidendritic). Periphytons  is a passive moving organisms, the type and density of periphyton is influenced by water quality. Periphytons is also a water quality bioindicator. This research aims to determine the type and density of epidendritic periphyton in the swamp of Sawah Village, has been conducted from May to June 2018. Epidendritic periphyton Sampling was carried out three times, once/ two week for two month. There were 72 types of periphyton presence, they were belonged to 7 classes of Phytoperiphyton, namely Bacillariophyceae (15 species), Chlorophyceae (31 species), Cyanophyceae (11 species), Chrysophyceae (2 species), Dinophyceae (1 species), Euglenophyceae (3 species), and 3 classes Zooperiphyton, namely Monogononta (8 species), Tubulinea (1 species). Phytoperiphyton abundance was 22,031 – 23,152 cells/cm2 and Zooperiphyton 133 – 336 organisms/cm2. The periphytons Diversity index (H') was 3.08 – 4.07; Domination Index (C) was 0.07 – 0.39; Uniformity Index (E) was 0.64 – 0.76. The water quality parameters are as follows, temperature was 27 - 29 °C, brightness was 42 - 65 cm, pH 5, CO2 was 13 - 15 mg/L, oxygen was 4.16 – 5.51 mg/L, nitrate was 0.14 – 0.21 mg/L, phosphate was 0.17 – 2.79 mg/L. Based on the epidendritic periphyton species and density, it can be concluded that the aquatic environment of swamp waters can be categorized as good.